Silica-immobilized ionic liquid Brønsted acids as highly effective heterogeneous catalysts for the isomerization of n-heptane and n-octane. Issue 26 (17th April 2020) - Dhar, Abhishek; Siva Kumar, Nadavala; Khimani, Mehul; Al-Fatesh, Ahmed S.; Ibrahim, Ahmed A.; Fakeeha, Anis H.; Patel, Hiren; Vekariya, Rohit L.
Abstract : Metal-free imidazolium-based ionic liquid (IL) Brønsted acids 1-methyl imidazolium hydrogen sulphate [HMIM]HSO4 and 1-methyl benzimidazolium hydrogen sulphate [HMBIM]HSO4 were synthesized. Abstract : Metal-free imidazolium-based ionic liquid (IL) Brønsted acids 1-methyl imidazolium hydrogen sulphate [HMIM]HSO4 and 1-methyl benzimidazolium hydrogen sulphate [HMBIM]HSO4 were synthesized. Their physicochemical properties were investigated using spectroscopic and thermal techniques, including UV-Vis, FT-IR, 1 H NMR, 13 C-NMR, mass spectrometry, and TGA. The ILs were immobilized on mesoporous silica gel and characterized by FT-IR spectroscopy, scanning electron microscopy, Brunauer–Emmett–Teller analysis, ammonia temperature-programmed desorption, and thermogravimetric analysis. [HMIM]HSO4 @silica and [HMBIM]HSO4 @silica have been successfully applied as promising replacements for conventional catalysts for alkane isomerization reactions at room temperature. Isomerization of n -heptane and n -octane was achieved with both catalysts. In addition to promoting the isomerization of n -heptane and n -octane (a quintessential reaction for petroleum refineries), these immobilized catalysts are non-hazardous and save energy.